The molecular annealing mechanisms of H. sapiens HelQ - Lou-Hing, Anna (2024)
The human genome is constantly under the threat of DNA damage as replicating cells are chemically exposed, resulting in double-strand breaks (DSBs). Humans evolved unique mechanisms for controlling these mutagenic effects. Homologous recombination (HR) repairs otherwise lethal DNA double-strand breaks. In mammals, multiple forms of HR have evolved for different contexts, including to underpin DNA replication so that genome duplication is completed before cell division. HR in this context is mutagenic, because it relies on unstable DNA synthesis by 'Break-Induced Replication' (BIR) within specialized HR DNA structures called D-loops. The extent of D-loop DNA synthesis can be restrained to the DNA break region to limit mutagenesis, but by mechanisms unknown in human cells. Genome instability is a hallmark of cancer, and if left untreated can be detrimental. Therefore, characterizing the role helicase proteins, namely HelQ, play in DNA repair and replication is of great importance.